Exploring the nexus between sectoral stock market fluctuations and macroeconomics changes before and during the COVID-19 pandemic - Suriani, S.; Correia, A. B.; Nasir, M.; Rita, J. X.; Saputra, J.; Mata, M. N. (Cogent Business and Management, 2024)
Investors may find it challenging to invest due to economic fluctuations during COVID-19. This study aims to examine the relationship between economic fluctuations and the Indonesian sectoral stock market in the consumer goods sector (CGI), basic industrial and chemical sector (BIC), and miscellaneous industry (MSI), both before and during the COVID-19 pandemic in Indonesia. The monthly time-series data used in the empirical approach cover the period from January 2008 to December 2020. The analysis used forecast error variance decomposition, vector autoregression, impulse response function analysis, and causality investigation. The econometric results showed that previous period shocks in each industrial sector stock market had a disadvantageous effect on future stock market earnings. Additionally, while the CGI stock market positively affects the Rupiah exchange rate, the MSI industrial sector is negatively impacted by inflationary pressures. Also connected to the MSI stock market are fluctuations in inflation. Conversely, the exchange rate affects MSI and CGI. Furthermore, for the CGI and BIC stock markets, a one-way causation relationship is observed. Another notable result was that all three industrial sectors responded positively when inflation and exchange rates were disrupted. It implies that, for convenience, investors will seek out other areas of the stock market. Therefore, a quick government response is needed to handle the economy during economic fluctuations accompanied by the COVID-19 pandemic so that it does not have an impact on the future.